2016
DOI: 10.1111/jch.12801
|View full text |Cite
|
Sign up to set email alerts
|

Serum Beta‐Trace Protein as a Novel Predictor of Pregnancy‐Induced Hypertension

Abstract: 4Beta-trace protein (BTP) has emerged as a novel biomarker of cardiovascular risk. However, the level of circulating BTP in pregnancy-induced hypertension (PIH) is still unknown. The aim of this study was to determine the concentration of serum BTP in healthy pregnant women and patients with PIH. No significant difference was found in the serum concentration of BTP in patients with a normal pregnancy. In contrast, serum BTP levels in women with PIH (n=46) were significantly higher than those in women with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…More recently, it has been reported that serum level of L-PGDS may represent a biomarker of kidney function ( White et al, 2015 ), pregnancy-induced hypertension ( Duan et al, 2016 ), and active lupus nephritis ( Brunner et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been reported that serum level of L-PGDS may represent a biomarker of kidney function ( White et al, 2015 ), pregnancy-induced hypertension ( Duan et al, 2016 ), and active lupus nephritis ( Brunner et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the kidneys eliminate BTP by glomerular filtration, and renal failure patients have increased serum BTP values 35 50 51 52 53 . Most recently, BTP has emerged as a novel biomarker of cardiovascular risk, and different studies have explored the role of BTP in hypertension 54 55 56 57 . Thus, increased BTP levels might also reflect injuries in the renal tubules and arterioles due to extended hypertension 58 59 .…”
Section: Beta-trace Proteinmentioning
confidence: 99%